1996
DOI: 10.1002/qj.49712253207
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ozone and thermal tropopause heights and the impact of tropopause definition on quantifying the ozone content of the troposphere

Abstract: A comparison has been conducted of the height and sharpness of the tropopause as revealed by temperature and ozone profiles. In the study, 628 ECC-type ozonesonde profiles from four stations in northern Europe were used. Two tropopauses were defined for each profile: a thermal tropopause and an ozone tropopause defined in terms of both mixing ratio and vertical gradient of mixing ratio. On average, the ozone tropopause lay 800 m below the thermal. Large differences in tropopause height were associated with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
148
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(166 citation statements)
references
References 13 publications
13
148
0
5
Order By: Relevance
“…13 also makes clear, the transition is not abrupt and occurs across a region several km deep which exhibits both tro- pospheric and stratospheric chemical characteristics. In particular, ozone does not reach characteristic tropospheric values until almost 1 km below the tropopause (lower left panel), a fact noted a decade ago by Bethan et al (1996) from ozonesonde measurements. On the other hand water vapor does not reach characteristic stratospheric values until about 2 km above the tropopause (lower right panel).…”
Section: July 2007 Tg Shepherdmentioning
confidence: 89%
“…13 also makes clear, the transition is not abrupt and occurs across a region several km deep which exhibits both tro- pospheric and stratospheric chemical characteristics. In particular, ozone does not reach characteristic tropospheric values until almost 1 km below the tropopause (lower left panel), a fact noted a decade ago by Bethan et al (1996) from ozonesonde measurements. On the other hand water vapor does not reach characteristic stratospheric values until about 2 km above the tropopause (lower right panel).…”
Section: July 2007 Tg Shepherdmentioning
confidence: 89%
“…Another tropopause definition in use is based on ozone (O 3 ), which shows a sharp transition from low concentrations in the troposphere to high concentrations in the stratosphere. The O 3 tropopause is usually somewhat lower than the thermal one [Bethan et al, 1996].…”
Section: Tropopausementioning
confidence: 98%
“…This allows localization, without ambiguity, of stratospheric and tropospheric air [Marenco et With the O3/PV estimates above, 'this corresponds to an ozone critical value ranging from 60 to 120 ppbv. Finally, a more sophisticated tropopause characterization has been elaborated by Bethan et al [ 1996] with (1) a vertical ozone gradient greater than 60 ppbv/km; (2) PV above 1.6-2 pvu; (3) ozone concentration higher than 80 ppbv; and (4) an ozone mixing ratio just above the tropopause higher than 110 ppbv. However, MOZAIC data at cruise level do not provide information on the vertical ozone gradient or tropopause altitude at the sampling position.…”
Section: Separation Between Stratospheric and Tropospheric Airmentioning
confidence: 99%
“…The rough 100 ppbv criterion, retained here, will be further improved by considering also values of th.e potential vorticity (PV), when available in the MOZAIC databank, and MOZAIC relative humidity (RH). However, the PV criterion of 2 pvu at the tropopause, used by the European Centre for Medium-Range Weather Forecasts (ECMWF) to specify the tropopause altitude, has to be reconsidered because various studies [Hoerling et al, 1991;Bethan et al, 1996] have shown seasonal variations and larger values of the PV (2.5 to 3.5 pvu) at the tropopause level. A local study of chemical, dynamic, and thermal tropopauses from 1650 MOZAIC profiles near Frankfurt (1994)(1995)(1996) thus indicates that ozone concentration at the chemical tropopause varies from 51 ppbv in winter to 75 ppbv in summer and that PV values at chemical/thermal tropopauses amount to 2.4 / 3 pvu in winter, and 3 / 3.7 pvu in summer, respectively.…”
Section: Separation Between Stratospheric and Tropospheric Airmentioning
confidence: 99%